Calculus for dummies - Ryan, Mark, 1955- (--For dummies., 2014)
This hands-on guide makes calculus manageable-- even if it makes you sweat! Ryan leads you step-by-step through each concept, operation, and solution, explaining the "how" and "why" in plain English.